Relative income, the breadwinner norm, and mental health in couples - Demid Getik (Lund University, School of Economics and Management, Department of Economics, 2022)
The share of couples where the wife out-earns the husband is increasing in many countries. In this paper, I investigate how this income dynamic affects mental health. Using data on all Swedish couples who married in 2001, I show that mental health is positively associated with own and spousal income. However, it is negatively linked to the wife's relative income. Crossing the threshold where the wife starts earning more increases the likelihood of a mental health diagnosis by 8-12 per cent. This effect does not appear driven by divorce or spouses being on different income trajectories.
Keywords: I12; I19; I21; I31; J16; J24; 330; gender; mental health; income; relative income